Analytical thinking ability: Implementation of modified free inquiry (mfi) learning models on environmental pollution - Sigit, Diana Vivanti; Budi, Agung Satiya; Miarsyah, Mieke (Biosfer: Jurnal Pendidikan Biologi, 2024)
Students' analytical thinking skills need to be developed and improved in biology learning. The lack of varied learning models used in learning makes students feel bored in learning. The modified free inquiry (MFI) learning model is one of the learning models that is thought to be suitable for improving students' analytical thinking skills. This study aims to determine and analyzed the effect of the application of the MFI learning model on students' analytical thinking skills on environmental pollution material. The method used in this research is quasi-experiment with the research design, namely pre-test and post-test control group design, and the sample used is 60 class X students. The data showed gain score in both classes is normally distributed and homogeneous. This research showed that MFI learning model effected the students' analytical thinking skills on environmental pollution. The application of the MFI learning model could be an alternative for teachers to improve students' analytical thinking skills, because this model encourages students' activeness in constructing knowledge so that it creates a meaningful learning experience.